Gas diffusion layer with gradient pore structure and preparation method thereof
By adopting gradient pore structure design and new preparation methods in the fuel cell gas diffusion layer, the gas transmission and drainage problems caused by the single structure of the traditional gas diffusion layer are solved, efficient gas diffusion and water management are achieved, and the performance of fuel cells is improved.
Patent Information
- Application Number
- CN202510009246.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-08
AI Technical Summary
The traditional gas diffusion layer has a single pore structure, which is difficult to meet the needs of rapid gas diffusion and effective drainage at the same time, resulting in large gas transmission resistance and flooding, limiting the performance of fuel cells.
Using gradient pore structure design, carbon fiber paper is sonicated and polystyrene and polymethyl methacrylate microspheres of different diameters are added to form a stacked structure of large, medium and microporous layers. Combined with rare earth salts and hydrophobic agent emulsions, a gas diffusion layer is prepared by hot pressing and sintering processes.
The efficient gas transmission and water management of the gas diffusion layer are realized, the overall performance of the fuel cell is improved, including higher voltage and power density, and the mechanical stability and conductivity of the material are also improved.
Smart Images

Figure CN119786642A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fuel cells, and in particular to a gas diffusion layer with a gradient pore structure and a preparation method thereof. Background Art
[0002] As the global demand for clean energy grows, fuel cells, as an efficient and clean energy conversion device, have attracted widespread attention. Fuel cells directly convert the chemical energy of fuel (such as hydrogen) and oxidant (such as oxygen) into electrical energy through electrochemical reactions. They have the advantages of high energy conversion efficiency and environmental friendliness, and show great application potential in electric vehicles, distributed power generation and other fields.
[0003] However, the performance of fuel cells is limited by multiple factors, among which the gas diffusion layer (GDL) is one of the key components. The gas diffusion layer has multiple important functions in fuel cells. It not only provides a gas transmission channel for the electrode reaction, ensuring that the reaction gases (hydrogen and oxygen) can quickly and effectively reach the catalyst layer to participate in the reaction, but also is responsible for exporting the water generated by the reaction to avoid flooding, and at the same time provides a conductive path for electron transfer.
[0004] Traditional gas diffusion layers usually use materials such as carbon fiber paper or carbon cloth. Although these materials have certain conductivity and mechanical strength, they are insufficient in gas diffusion performance. Their pore structure is often relatively simple and cannot meet the needs of rapid gas diffusion and effective drainage at the same time. In the actual operation of the fuel cell, the reaction gas needs to pass through the gas diffusion layer to reach the catalyst layer under a certain pressure. The gas diffusion layer with a single pore structure may lead to a large gas transmission resistance, especially under high current density conditions, where insufficient gas supply will seriously limit the power output of the fuel cell. Moreover, poor drainage capacity will cause the generated water to accumulate in the gas diffusion layer, blocking the gas transmission channel and further deteriorating the battery performance.
[0005] In order to overcome these problems of traditional gas diffusion layers, the design concept of gradient pore structure came into being. In the gradient pore structure, macropores are mainly responsible for rapid gas transmission, which can achieve macroscopic diffusion of gas at a lower pressure, so that the reaction gas can diffuse rapidly in the gas diffusion layer; mesopores can play a transitional role between macropores and micropores, balancing gas transmission and water management; micropores can increase the contact area between the gas diffusion layer and the catalyst layer, promote the effective adsorption and reaction of gas on the surface of the catalyst layer, and also help to improve the mechanical stability of the gas diffusion layer. This gradient pore structure can be optimized according to actual needs, so that the gas diffusion layer can maintain good gas diffusion and water management capabilities under different working conditions, thereby improving the overall performance of the fuel cell.
[0006] At present, the method for preparing a gas diffusion layer with a gradient pore structure is still imperfect. Some existing preparation processes either have difficulty in accurately controlling the size and distribution of pores, resulting in an unsatisfactory gradient pore structure, or the process is complicated and costly, which is not conducive to large-scale production. Therefore, there is an urgent need for a new preparation method that can easily, efficiently and cost-effectively prepare a fuel cell gas diffusion layer with an ideal gradient pore structure to meet the fuel cell industry's demand for high-performance gas diffusion layers and promote the further development and commercial application of fuel cell technology. Summary of the invention
[0007] In order to solve the problems of the existing gas diffusion layer, such as unsatisfactory gradient pore structure, easy flooding, low mass transfer efficiency, and complicated preparation method, the present invention provides a gas diffusion layer with a gradient pore structure and a preparation method thereof, which are as follows:
[0008] A method for preparing a gas diffusion layer having a gradient pore structure comprises the following steps:
[0009] Step 1: soak the carbon fiber paper in a mixed solution of a hydrophobic agent emulsion and anhydrous ethanol and perform ultrasonic treatment so that the hydrophobic agent emulsion is evenly dispersed and adsorbed on the carbon fiber paper, and then the carbon fiber paper is dried to obtain a carbon fiber base layer;
[0010] Step 2: Take polystyrene (PS) microspheres with a diameter of 500-800nm and polymethyl methacrylate (PMMA) microspheres with a diameter of 600-900nm, add them to anhydrous ethanol solution for ultrasonic treatment, then add a conductive agent and a rare earth salt, stir evenly, add a hydrophobic agent emulsion, continue to stir evenly, and obtain a first specification slurry with a total microsphere concentration of 20-26g / L; the total microspheres refer to the sum of the two types of microspheres in the slurry: polystyrene microspheres and polymethyl methacrylate.
[0011] Step 3: taking polystyrene microspheres with a diameter of 200-500 nm and polymethyl methacrylate microspheres with a diameter of 250-550 nm, adding them to an anhydrous ethanol solution for ultrasonic treatment, then adding a conductive agent and a rare earth salt, stirring evenly, adding a hydrophobic agent emulsion, and continuing to stir evenly to obtain a second specification slurry with a total microsphere concentration of 18-20 g / L;
[0012] Step 4: taking polystyrene microspheres with a diameter of 80-200 nm and polymethyl methacrylate microspheres with a diameter of 100-220 nm, adding them to an anhydrous ethanol solution for ultrasonic treatment, then adding a conductive agent and a rare earth salt, stirring evenly, adding a hydrophobic agent emulsion, and continuing to stir evenly to obtain a third specification slurry with a total microsphere concentration of 14-17 g / L;
[0013] Step 5: uniformly coating the obtained first specification slurry on the surface of the carbon fiber base layer to obtain a first layer, and then drying it; then coating and drying the second specification slurry on the first layer to obtain a second layer, and then coating and drying the third specification slurry on the second layer to finally obtain a slurry laminated structure;
[0014] Step 6: hot pressing the slurry stack structure, sintering the hot pressed sample at high temperature, and then washing and drying to obtain a gas diffusion layer;
[0015] The mass of the polystyrene microspheres added in step 2-4 is greater than the mass of the polymethyl methacrylate microspheres, and the diameters of the polystyrene microspheres and the polymethyl methacrylate microspheres are different.
[0016] Preferably, the conductive agent and rare earth salt of the same substance are added in steps 2-4, the hydrophobic agent emulsion in steps 1-4 is of the same substance, and the conductive agent, rare earth salt and hydrophobic agent emulsion added in steps 2-4 are the same or different in amount.
[0017] Preferably, the diameter of the polymethyl methacrylate microspheres added in each of steps 2-4 is not less than the diameter of the polystyrene microspheres.
[0018] Furthermore, in step 1, the volume ratio of the hydrophobic agent emulsion to anhydrous ethanol is 1:5-1:10, the ultrasonic time is 15-30 minutes, the drying temperature is 80-120° C., and the drying time is 1-2 hours.
[0019] Furthermore, the hydrophobic agent emulsion in steps 1-4 is one or more of polytetrafluoroethylene (PTFE) emulsion, polyvinylidene fluoride emulsion, and polyvinylidene fluoride emulsion, and the mass ratio of total microspheres to hydrophobic agent emulsion in steps 2-4 is 1:0.5-1:2.5.
[0020] Furthermore, the rare earth salt in step 2-4 is one or more of cerium nitrate, lanthanum nitrate, praseodymium nitrate, neodymium nitrate, and europium nitrate, and the mass ratio of total microspheres to rare earth salt is 1:0.05-1:0.25.
[0021] Furthermore, the conductive agent in step 2-4 is one or more of carbon black, acetylene black, Ketjen black, and graphite powder, and the mass ratio of total microspheres to conductive agent is 1:0.3-1:0.8.
[0022] Furthermore, the mass ratio of the polystyrene microspheres to the polymethyl methacrylate microspheres added in step 2 is 1:0.6-1:0.8, in step 3 it is 1:0.6-1:0.9, and in step 4 it is 1:0.7-1:0.8.
[0023] Furthermore, in step 5, the coating thickness of the first specification slurry>the coating thickness of the second specification slurry>the coating thickness of the third specification slurry.
[0024] Furthermore, the hot pressing process in step 6 is specifically as follows: the hot pressing temperature is 140-250° C., the pressure is 8-15 MPa, and the holding time is 8-20 min.
[0025] Furthermore, the sintering process in step 6 is specifically as follows: starting from room temperature, heating to 350-500° C. at a heating rate of 5-10° C. / min, and keeping the temperature for 2-4 hours.
[0026] The gas diffusion layer with a gradient pore structure prepared according to the above preparation method includes a carbon fiber base layer and a microporous layer, the microporous layer includes a macroporous layer with a pore size of 500-900nm, a mesoporous layer with a pore size of 200-550nm and a microporous layer with a pore size of 80-220nm, in the order of carbon fiber base layer, macroporous layer, mesoporous layer and microporous layer.
[0027] Beneficial effects of the present invention:
[0028] (1) The present invention constructs a gas diffusion layer with an interconnected gradient pore structure, in which the macropores are mainly responsible for rapid gas transmission and can achieve macroscopic diffusion of gas at a relatively low pressure, so that the reaction gas can diffuse rapidly in the gas diffusion layer; the mesopores can play a transitional role between the macropores and the micropores to balance the gas transmission; the small pores can increase the contact area between the gas diffusion layer and the catalyst layer, promote the effective adsorption and reaction of the gas on the surface of the catalyst layer, and also help to improve the mechanical stability of the gas diffusion layer.
[0029] (2) In the process of preparing the microporous layer slurry, the present invention simultaneously adds two pore-forming agents, PS microspheres and PMMA microspheres, which can improve the uniformity of pore distribution on the one hand: the mixed use of the two microspheres can make the pores in the gas diffusion layer more uniformly distributed, avoid excessive or too small local pore density, improve the consistency and stability of gas diffusion, and thus improve the performance in applications such as batteries; on the other hand, it can improve the properties of the pore wall: the surface properties of PMMA microspheres are different from those of PS microspheres, and the addition of PMMA microspheres can adjust the roughness, hydrophilicity and hydrophobicity of the pore wall, thereby optimizing the diffusion and transmission performance of the gas in the pores and improving the air permeability and drainage of the gas diffusion layer. In addition, the diameters of the two pore-forming agents, PS microspheres and PMMA microspheres, are different, and this size difference helps to form a gradient pore structure: larger PMMA microspheres can construct relatively large pore channels in the material, while smaller PS microspheres can fill the gaps between PMMA microspheres, so that the pores form a gradient change from large to small, and larger pores are conducive to rapid gas entry, while smaller pores can increase the contact area between the gas and the material, allowing the gas to diffuse better. At the same time, the mechanical properties of the material can be optimized: large-sized PMMA microspheres can play the role of supporting the skeleton, and small-sized PS microspheres filled in the gaps between them help enhance the stability of the structure, so that the gas diffusion layer can still maintain its structural integrity under a certain pressure and play a better role.
[0030] (3) In addition, the rare earth salt is added during the preparation of the microporous layer slurry in the present invention, which has the following effects:
[0031] i. Optimize pore structure: Rare earth ions in rare earth salt solutions can interact with pore formers (polystyrene microspheres and polymethyl methacrylate microspheres) and other substances, affecting the decomposition and volatilization process of the pore formers, thereby more accurately controlling the pore size and distribution. Combined with the pore formers themselves, abundant pores can be formed, which helps to form a more ideal gradient pore structure and improve gas diffusion efficiency.
[0032] ii. Improve electrical conductivity: Rare earth elements have unique electronic structures and chemical properties, which can increase the electronic conductivity of the gas diffusion layer, reduce resistance, reduce energy loss in electrochemical devices such as batteries or electrolytic cells, and improve energy conversion efficiency.
[0033] iii. Enhanced stability: After adding rare earth salts, during the preparation of the gas diffusion layer, rare earth elements can form more stable chemical bonds or interactions with other materials, making the structure of the gas diffusion layer more stable. At the same time, the substances produced by the decomposition of the pore-forming agent or the supporting role played by the pore-forming agent itself in the gas diffusion layer can improve the chemical stability and structural stability of the gas diffusion layer in complex environments, such as anti-corrosion, anti-oxidation, and anti-wear properties, and extend its service life.
[0034] iv. Improve catalytic activity: Rare earth elements can change the electronic structure and surface properties of the catalyst. When used as a catalyst carrier in the gas diffusion layer, they can improve the dispersion and activity of the catalyst, accelerate the chemical reaction rate, and improve the efficiency and selectivity of related chemical reactions. At the same time, they can work together with pore-forming agents to increase the specific surface area of the gas diffusion layer, provide more attachment sites for the catalyst, increase the number of active sites for the electrochemical reaction, and improve battery performance.
[0035] v. Increase hydrophilicity and hydrophobicity: The addition of rare earth salt solution can adjust the surface energy of the gas diffusion layer, thereby affecting its hydrophilicity and hydrophobicity, so that the gas diffusion layer can better control the penetration and transmission of liquid while maintaining good air permeability, optimize the gas-liquid-solid three-phase interface, and improve the performance of the electrochemical device.
[0036] (4) The prepared gas diffusion layer has a large porosity, pore volume and specific surface area. The porosity is greater than 78%, the pore volume is greater than 1.7 cc / g, and the specific surface area is greater than 380 cm 2 / g, showing excellent performance in electrochemical devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] The embodiments of the present invention are further described below with reference to the accompanying drawings, in which:
[0038] Figure 1 The schematic diagram of the structure of the gas diffusion layer with gradient pore structure of the present invention is shown;
[0039] Figure 2 The performance comparison diagram (voltage-current density) of the gas diffusion layer of Examples 1-3 of the present invention and Comparative Examples 1 and 2 is shown;
[0040] Figure 3 A performance comparison diagram (power density-current density) of the gas diffusion layers of Examples 1-3 of the present invention and Comparative Examples 1 and 2 is shown. DETAILED DESCRIPTION
[0041] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below through specific embodiments in conjunction with the accompanying drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0042] Example 1
[0043] (1) 10×10 cm carbon fiber paper was soaked in a mixed solution of 20 mL PTFE emulsion and 100 mL anhydrous ethanol, and ultrasonically treated for 20 min to make the PTFE emulsion evenly dispersed and adsorbed on the carbon fiber paper. It was then dried at 100°C for 2 h to obtain a carbon fiber base layer.
[0044] (2) Preparation of gradient pore-forming slurry:
[0045] Prepare the first specification slurry (macroporous layer slurry): add 1g of PS microspheres with a diameter of 600nm and 0.8g of PMMA microspheres with a diameter of 700nm into 70ml of anhydrous ethanol and disperse them by ultrasonic for 1h. Add 0.67g of carbon black and 0.1g of cerium nitrate, stir evenly, then add 1g of PTFE emulsion and continue stirring to form a macroporous slurry;
[0046] Prepare the second specification slurry (mesoporous layer slurry): put 0.7g of PS microspheres with a diameter of 400nm and 0.6g of PMMA microspheres with a diameter of 500nm into 70ml of anhydrous ethanol and ultrasonicate for 1h. Then add 0.67g of carbon black and 0.1g of cerium nitrate, stir evenly, then add 1g of PTFE emulsion and stir to make a mesoporous slurry;
[0047] The third specification slurry (microporous layer slurry) was prepared by ultrasonicating 0.5 g of PS microspheres with a diameter of 150 nm and 0.4 g of PMMA microspheres with a diameter of 200 nm in 60 ml of anhydrous ethanol for 1 h. Then, 0.66 g of carbon black and 0.1 g of cerium nitrate were added, stirred evenly, and 1 g of PTFE emulsion was added, stirred to form a microporous slurry.
[0048] Adding the conductive agent and rare earth salt first can make them fully dispersed in the slurry, avoiding the influence of the presence of PTFE emulsion on the dispersion effect (PTFE emulsion will wrap the conductive agent and rare earth salt and cause agglomeration), thereby being more conducive to forming a uniform conductive network and exerting the role of rare earth salt, such as improving the catalytic performance or stability of the material.
[0049] In addition, PTFE emulsion mainly plays a hydrophobic role. Its later addition can more accurately control its content and distribution in the slurry, thereby better adjusting the hydrophobicity of the gas diffusion layer and avoiding problems such as reduced porosity or decreased conductivity due to excessive PTFE.
[0050] (3) Layered coating:
[0051] First, the first specification slurry (macroporous layer slurry) is evenly coated on the surface of the carbon fiber base layer with a scraper, and the coating thickness is controlled to be 0.18-0.22mm. Then it is placed in a constant temperature drying oven and dried at 80°C for 1 hour to evaporate part of the solvent. The slurry is initially shaped to obtain the first layer;
[0052] Then, the second specification slurry (mesoporous layer slurry) is coated on the dried first layer with a coating thickness of about 0.14-0.16 mm, and then placed in the drying oven again and dried under the same temperature and time conditions to make the two layers better bonded, thus obtaining the second layer;
[0053] Finally, the third specification slurry (microporous layer slurry) is coated on the second layer with a thickness controlled at 0.09-0.11 mm. After drying under the same conditions, a three-layer slurry laminated structure with different potential pore structures is completed.
[0054] (4) Compaction treatment:
[0055] The slurry laminate structure was compacted using a hot press, with the hot press temperature set to 200°C, the pressure set to 8 MPa, and the holding time set to 10 minutes.
[0056] (5) Pore treatment:
[0057] The compacted structure is placed in a muffle furnace for high-temperature sintering to remove the pore-forming agent and form pores. The temperature is raised from room temperature to 400°C at a rate of 5°C / min and kept at this temperature for 2 hours to fully decompose and volatilize the polystyrene microspheres and polymethyl methacrylate microspheres, leaving corresponding gradient pores inside the material, thereby obtaining a gas diffusion layer with a gradient pore structure.
[0058] Finally, the sintered gas diffusion layer is rinsed several times with deionized water to remove residual impurities, incompletely decomposed pore-forming agents, etc. After rinsing, it is dried in a vacuum drying oven at 80° C. for 8 hours to make it completely dry.
[0059] Example 2
[0060] Preparation of macroporous layer slurry: Add 0.9g PS microspheres with a diameter of 700nm and 0.7g PMMA microspheres with a diameter of 800nm into 70ml anhydrous ethanol and disperse them by ultrasonic for 1h. Add 0.7g carbon black and 0.15g europium nitrate, stir evenly, then add 1g PTFE emulsion and continue stirring to form macroporous slurry;
[0061] Preparation of mesoporous slurry: 0.8g of PS microspheres with a diameter of 500nm and 0.5g of PMMA microspheres with a diameter of 450nm were placed in 70ml of anhydrous ethanol and ultrasonicated for 1h. Then, 0.65g of carbon black and 0.1g of europium nitrate were added, stirred evenly, and 1g of PTFE emulsion was added to prepare mesoporous slurry;
[0062] Preparation of microporous slurry: 0.5 g of PS microspheres with a diameter of 200 nm and 0.4 g of PMMA microspheres with a diameter of 210 nm were ultrasonicated in 60 ml of anhydrous ethanol for 1 h. Then, 0.7 g of carbon black and 0.15 g of europium nitrate were added, stirred evenly, and 1.5 g of PTFE emulsion was added to obtain microporous slurry.
[0063] The remaining steps and process parameters are the same as those in Example 1, and a gas diffusion layer with a gradient pore structure is obtained.
[0064] Example 3
[0065] Preparation of macroporous layer slurry: Add 0.8g of PS microspheres with a diameter of 800nm and 0.6g of PMMA microspheres with a diameter of 900nm into 70ml of anhydrous ethanol and disperse them by ultrasonic for 1h. Add 0.68g of carbon black and 0.12g of lanthanum nitrate, stir evenly, then add 1.5g of PTFE emulsion and continue stirring to form a macroporous slurry;
[0066] Preparation of mesoporous slurry: 0.7g of PS microspheres with a diameter of 450nm and 0.6g of PMMA microspheres with a diameter of 400nm were placed in 70ml of anhydrous ethanol and ultrasonicated for 1h. Then, 0.66g of carbon black and 0.12g of lanthanum nitrate were added, stirred evenly, and 1g of PTFE emulsion was added to prepare a mesoporous slurry;
[0067] Preparation of microporous slurry: 0.5 g of PS microspheres with a diameter of 80 nm and 0.4 g of PMMA microspheres with a diameter of 100 nm were ultrasonicated in 60 ml of anhydrous ethanol for 1 h. Then, 0.7 g of carbon black and 0.2 g of lanthanum nitrate were added, stirred evenly, and 2 g of PTFE emulsion was added to obtain microporous slurry.
[0068] The remaining steps and process parameters are the same as those in Example 1, and a gas diffusion layer with a gradient pore structure is obtained.
[0069] Comparative Example 1
[0070] Soak the carbon paper in 11wt.% PTFE emulsion for 10 minutes, take it out and put it in a 120℃ oven to dry. After the carbon paper is completely dried, put it in a muffle furnace and heat treat it at 400℃ for 45 minutes. Weigh the mass to obtain 20wt.% polytetrafluoroethylene carbon paper. Put the carbon paper in 20wt.% polytetrafluoroethylene emulsion and treat it with the above method to obtain 30wt.% polytetrafluoroethylene carbon paper. Weigh carbon black, 10wt.% polytetrafluoroethylene emulsion and isopropanol in sequence to make the mass ratio of 7:30:100, stir for 2h after mixing, and ultrasonically disperse for 2h to mix the carbon black and polytetrafluoroethylene evenly. Use the flat end of the weighing spoon to scrape the carbon black onto the 30wt.% polytetrafluoroethylene carbon paper, weigh it after drying, and repeat until the carbon black loading reaches 2.5mg / cm 2 , put it in a muffle furnace and heat treat it at 400℃ for 30min to obtain a gas diffusion layer.
[0071] Comparative Example 2
[0072] Preparation of macroporous layer slurry: Add 1g of PS microspheres with a diameter of 600nm into 70ml of anhydrous ethanol and disperse them by ultrasonic for 1h. Add 0.67g of carbon black, stir evenly, then add 1g of PTFE emulsion and continue stirring to form a macroporous slurry;
[0073] Preparation of mesoporous slurry: 0.7g of PS microspheres with a diameter of 400nm was placed in 70ml of anhydrous ethanol and ultrasonicated for 1h. Then 0.67g of carbon black was added, stirred evenly, and 1g of PTFE emulsion was added to prepare mesoporous slurry;
[0074] Preparation of microporous slurry: 0.5 g of PS microspheres with a diameter of 150 nm were ultrasonicated in 60 ml of anhydrous ethanol for 1 h. Then 0.66 g of carbon black was added, stirred evenly, and 1 g of PTFE emulsion was added to obtain microporous slurry.
[0075] The remaining steps and process parameters are the same as those in Example 1, and a gas diffusion layer with a gradient pore structure is obtained.
[0076] Performance Testing
[0077] The gas diffusion layers prepared in Examples 1-3 and Comparative Examples 1 and 2 were analyzed and characterized. The porosity, pore volume and specific surface area results are shown in Table 1. At the same time, the prepared gas diffusion layer assembled MEA was tested. The test conditions were: temperature of 85°C, cathode and anode gas inlet stoichiometric ratio of 1.5 / 2.0, cathode and anode back pressure of 120 kPa / 50 kPa, hydrogen side and air side flow rates of 0.4 / 0.7 L / M, and the test was carried out at a humidity of 45%. The performance test results are shown in Table 1. Figure 2 and Figure 3 As shown. From the results of the above embodiments and comparative examples, it can be seen that the gas diffusion layer prepared by the method of the present invention by adding PS microspheres, PMMA microspheres and rare earth salts has better performance: at the same current density, the gas diffusion layer prepared by the present invention has higher voltage and power density, thanks to its gradient pore structure, which improves the drainage and gas conductivity of the gas diffusion layer.
[0078] Table 1 Porosity, pore volume and specific surface area results
[0079] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Porosity (%) 78.2 78.6 79.1 71.2 75.5 Pore volume (cc / g) 1.73 1.74 1.76 1.20 1.55 <![CDATA[Specific surface area (cm 2 / g)]]> 380 395 410 150 275
[0080] Some exemplary embodiments of the present invention are described above. It can be understood that the above embodiments are only used to explain the present invention and do not constitute a limitation on the protection scope of the present invention. The features in these embodiments can be recombined in a suitable manner, and the scheme obtained thereby is still within the protection scope required by the present invention. Based on the above embodiments, all other embodiments obtained by those skilled in the art without making creative work, that is, all modifications, equivalent substitutions and improvements made within the spirit and principles of this application, fall within the protection scope required by the present invention.
Claims
1. A method for preparing a gas diffusion layer having a gradient pore structure, characterized in that: The following steps are involved: Step 1: soaking the carbon fiber paper in a mixed solution of a hydrophobic agent emulsion and anhydrous ethanol for ultrasonic treatment, and then drying the carbon fiber paper to obtain a carbon fiber base layer; Step 2: polystyrene microspheres with a diameter of 500-800 nm and polymethyl methacrylate microspheres with a diameter of 600-900 nm are added to an anhydrous ethanol solution for ultrasonic treatment, and then a conductive agent and a rare earth salt are added. After stirring evenly, a hydrophobic agent emulsion is added and stirring is continued to obtain a first specification slurry with a total microsphere concentration of 20-26 g / L; Step 3: adding polystyrene microspheres with a diameter of 200-500 nm and polymethyl methacrylate microspheres with a diameter of 250-550 nm to an anhydrous ethanol solution for ultrasonic treatment, and preparing a second specification slurry with a total microsphere concentration of 18-20 g / L in the same manner as in step 2; Step 4: adding polystyrene microspheres with a diameter of 80-200 nm and polymethyl methacrylate microspheres with a diameter of 100-220 nm to an anhydrous ethanol solution for ultrasonic treatment, and preparing a third specification slurry with a total microsphere concentration of 14-17 g / L in the same manner as in step 2; Step 5: uniformly coating the obtained first specification slurry on the surface of the carbon fiber base layer to obtain a first layer, and then drying it; Then, a second-specification slurry is coated and dried on the first layer to obtain a second layer, and a third-specification slurry is coated and dried on the second layer to finally obtain a slurry laminated structure; Step 6: hot pressing the slurry stack structure, sintering the hot pressed sample at high temperature, and then washing and drying to obtain a gas diffusion layer; The mass of the polystyrene microspheres added in step 2-4 is greater than the mass of the polymethyl methacrylate microspheres, and the diameters of the polystyrene microspheres and the polymethyl methacrylate microspheres are different.
2. The method for preparing a gas diffusion layer having a gradient pore structure according to claim 1, characterized in that: In step 1, the volume ratio of the hydrophobic agent emulsion to anhydrous ethanol is 1:5-1:10, the ultrasonic time is 15-30 minutes, the drying temperature is 80-120° C., and the drying time is 1-2 hours.
3. The method for preparing a gas diffusion layer having a gradient pore structure according to claim 1, characterized in that: The hydrophobic agent emulsion in steps 1-4 is one or more of polytetrafluoroethylene emulsion, polyvinylidene fluoride emulsion, and polyvinylidene fluoride emulsion. The mass ratio of total microspheres to hydrophobic agent emulsion in steps 2-4 is 1:0.5-1:2.
5.
4. The method for preparing a gas diffusion layer having a gradient pore structure according to claim 1, characterized in that: The rare earth salt in step 2-4 is one or more of cerium nitrate, lanthanum nitrate, praseodymium nitrate, neodymium nitrate, and europium nitrate, and the mass ratio of total microspheres to rare earth salt is 1:0.05-1:0.
25.
5. The method for preparing a gas diffusion layer having a gradient pore structure according to claim 1, characterized in that: The conductive agent in step 2-4 is one or more of carbon black, acetylene black, Ketjen black, and graphite powder, and the mass ratio of total microspheres to conductive agent is 1:0.3-1:0.
8.
6. The method for preparing a gas diffusion layer having a gradient pore structure according to claim 1, characterized in that: The mass ratio of the polystyrene microspheres to the polymethyl methacrylate microspheres added in step 2 is 1:0.6-1:0.8, in step 3 it is 1:0.6-1:0.9, and in step 4 it is 1:0.7-1:0.
8.
7. The method for preparing a gas diffusion layer having a gradient pore structure according to claim 1, characterized in that: In step 5, the coating thickness of the first specification slurry>the coating thickness of the second specification slurry>the coating thickness of the third specification slurry.
8. The method for preparing a gas diffusion layer having a gradient pore structure according to claim 1, characterized in that: The hot pressing process in step 6 is specifically as follows: the hot pressing temperature is 140-250° C., the pressure is 8-15 MPa, and the holding time is 8-20 min.
9. The method for preparing a gas diffusion layer having a gradient pore structure according to claim 1, characterized in that: The sintering process in step 6 is specifically as follows: starting from room temperature, heating up to 350-500° C. at a heating rate of 5-10° C. / min, and keeping the temperature for 2-4 hours.
10. A gas diffusion layer having a gradient pore structure obtained by the preparation method according to any one of claims 1 to 9, characterized in that: It includes a carbon fiber base layer and a microporous layer. The microporous layer includes a macroporous layer with a pore size of 500-900nm, a mesoporous layer with a pore size of 200-550nm and a microporous layer with a pore size of 80-220nm, and the order is carbon fiber base layer, macroporous layer, mesoporous layer and microporous layer.